Quantum‐dot‐based integrated non‐linear sources. Issue 2 (1st April 2015) - Bernard, Alice; Mariani, Silvia; Andronico, Alessio; Gerard, Jean‐Michel; Kamp, Martin; Jepsen, Peter‐Uhd; Leo, Giuseppe
Abstract : The authors report on the design and the preliminary characterisation of two active non‐linear sources in the terahertz and near‐infrared range. The former is associated to difference‐frequency generation between whispering gallery modes of an AlGaAs microring resonator, whereas the latter is granted by parametric generation in a waveguide via modal phase matching. Both devices rely on embedded quantum‐dot lasers, which allow for low‐threshold currents and unconventional geometries. They also include specific degrees of freedom that open a practical route towards phase matching, either during the lithographic process or during operation.